2019
DOI: 10.1590/1984-0462/;2019;37;3;00006
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pertussis in Childhood: Update and Controversy - Systematic Review

Abstract: Objective: Through a systematic review, this essay aimed at revising the concepts of severe pertussis, updating the epidemiology, pathophysiology, clinical presentation, antibiotic therapy and auxiliary therapeutic options for symptomatology and complications.Data sources:This review considered publications from the last 30years in the databases US National Library of Medicine (PubMed), Scientific Electronic Library Online (SciELO), Literatura Latino-americana e do Caribe em Ciências da Saúde (LILACS), Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
(146 reference statements)
0
15
0
1
Order By: Relevance
“…An observational study showed that this strategy conferred up to 90% protection for infants under 3 months from pertussis, by the dual effect of preventing maternal infection thereby minimizing mother-to-baby transmission, and also by virtue of specific IgG antibodies from the mother crossing the placenta affording protection to baby after birth [10][11][12][13]. In Argentina the deaths of pertussis cases deceased by 87% in 2013 compared to 2011, since the country implemented the strategy of acellular pertussis vaccination in pregnancy in 2012 [14].…”
Section: Discussionmentioning
confidence: 99%
“…An observational study showed that this strategy conferred up to 90% protection for infants under 3 months from pertussis, by the dual effect of preventing maternal infection thereby minimizing mother-to-baby transmission, and also by virtue of specific IgG antibodies from the mother crossing the placenta affording protection to baby after birth [10][11][12][13]. In Argentina the deaths of pertussis cases deceased by 87% in 2013 compared to 2011, since the country implemented the strategy of acellular pertussis vaccination in pregnancy in 2012 [14].…”
Section: Discussionmentioning
confidence: 99%
“…An observational study showed that this strategy conferred up to 90% protection for infants under 3 months from pertussis, by the dual effect of preventing maternal infection thereby minimizing mother-to-baby transmission, and also by virtue of speci c IgG antibodies from the mother crossing the placenta affording protection to baby after birth. [9,10,11,12]. In Argentina the deaths of pertussis cases deceased by 87% in 2013 compared to 2011, since the country implemented the strategy of acellular pertussis vaccination in pregnancy in 2012 [ 13].…”
Section: Discussionmentioning
confidence: 99%
“…It uses macrophages as an intracellular niche and that the intra macrophage phase of infection could play a significant role in survival and persistence of bacteria within the host 43 45 . Moreover, it has been reported that expression of IP-10 in mixed infections occurred earlier than in single infection possibly promoting a faster and stronger macrophage response 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite a high childhood vaccination rate, Bordetella pertussis (Bp) outbreaks occur periodically and Whooping cough–also known as Pertussis–remains a public health problem particularly for infants 1 3 and children, for whom it remains one of the most fatal infections 4 .…”
Section: Introductionmentioning
confidence: 99%